FOR THE SYNERGISTIC UNDERSTANDING OF MANAGEMENT DEVELOPMENT IN THE CONDITIONS OF GLOBALIZATION (Globalization and Business, 2018)
The article contains general and author’s paradigms, definitions and opinions related to the topic. It is worth mentioning:In economical and managerial sphere it is necessary to formulate new concepts and paradigms that will revive management sciences and practices;To prepare higher qualified managers: it is needed to prepare the appropriate educational-training system;In globalization, in civilized countries, based on the latest economic-management concepts and paradigms the relevant business-management theory and practice is developing, which must be taken into account in our country as well;To achieve sustainable development goals it is necessary to make major changes in planning and management areas;Ecological management is the process of mobilizing resources by the organization, which is intended to solve environmental problems;The concept of synergistic economics and management should be based on the work of each person and the whole community in economical and managerial works.